2021
DOI: 10.1002/pros.24115
|View full text |Cite
|
Sign up to set email alerts
|

Safety of concomitant therapy with radium‐223 and abiraterone or enzalutamide in a real‐world population

Abstract: Background Real‐world utilization and outcomes of combination therapy for men with metastatic castrate‐resistant prostate cancer (mCRPC) are largely unknown. We evaluated the overall survival (OS) and skeletal‐related events (SREs) among men who received radium‐223 with or without concomitant abiraterone or enzalutamide in the Veterans Affairs (VA) Health System. Methods We reviewed charts of all mCRPC patients who received radium‐223 in the VA from January 2013 to September 2017. We used Cox models to test th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…When 223 Ra monotherapy was compared with standard-of-care, the estimated 36-month fracture risk in the respective groups was 19% vs. 10% (HR 1.61; 95% CI: 0.96–3.02) ( 43 ). Regimens combining use of 223 Ra and abiraterone (plus prednisolone) or enzalutamide have been reported in real-world studies ( 44 48 ). However, based on a significantly increased risk of fractures when 223 Ra was used in combination with abiraterone plus prednisolone in the ERA 223 phase 3 RCT ( 49 ), this combination is now contraindicated in the EU ( 2 ) and is not recommended in the US ( 3 ).…”
Section: Safetymentioning
confidence: 99%
“…When 223 Ra monotherapy was compared with standard-of-care, the estimated 36-month fracture risk in the respective groups was 19% vs. 10% (HR 1.61; 95% CI: 0.96–3.02) ( 43 ). Regimens combining use of 223 Ra and abiraterone (plus prednisolone) or enzalutamide have been reported in real-world studies ( 44 48 ). However, based on a significantly increased risk of fractures when 223 Ra was used in combination with abiraterone plus prednisolone in the ERA 223 phase 3 RCT ( 49 ), this combination is now contraindicated in the EU ( 2 ) and is not recommended in the US ( 3 ).…”
Section: Safetymentioning
confidence: 99%
“…There was no significant difference in the incidence of SSEs among all groups ( Figure 2 , and Supplementary Table 1 and 2 ). 5 , 6 , 10 , 21 , 27 , 28 The pairwise comparison of SSEs and SSE-FS between the 223 Ra+NHA combination group and the 223 Ra monotherapy group did not yield significant differences (SMD: 0.11, 95% CI: −0.13–1.01, I 2 = 80%, P = 0.13; and ). 6 , 27 , 28 This result suggested that the use of 223 Ra combined with NHAs did not cause a higher incidence of SSEs or shorter SSE-FS.…”
Section: Resultsmentioning
confidence: 89%
“…Indeed, we previously showed that many men within this cohort were treated with concomitant radium and ARTA, though this did not impact OS. 20 Notably, some patients may have been diagnosed with mCRPC prior to the FDA approval of radium-223 and as such may potentially have received treatment later in the disease course than desired. We did not capture potential off-label use of radium-223 for patients with nonbony metastases due to our inclusion criteria.…”
Section: Discussionmentioning
confidence: 99%